Return on experience : learning leadership at work - Yip, Jeffrey (Ideas into action guidebooks., 2009)
"Leadership is best learned from experience, but learning from experience is not always automatic. This guidebook introduces you to a return-on-experience framework. Using the ROE framework, you actively seek to learn from experience in order to build your mastery, broaden your versatility, and benefit your organization. When you understand and apply the framework in your work and organization, everyday experiences can be transformed into an engine for leader development and organizational impact."--Publisher's website